Pengaruh Pengumuman PPKM Darurat terhadap Harga dan Return Saham Perbankan - Murharsito Murharsito (Jurnal Dinamika Ekonomi & Bisnis, 2021)
The massive transmission of the second wave pandemic of Covid-19 in Indonesia in June 2021 caused the Government to take a decision to impose an Emergency Java-Bali Community Activity Restriction (PPKM) aimed to minimize the effect of its spread. By using an event study, the objective of this article is to analyze the impact of announcement of public restrictions on the price and returns of stocks of the 5 largest banks in Indonesia, namely BCA, BNI, BRI, BTN, and MANDIRI. The analytical technique used was the paired sample T test and the Wilcoxon Signed Ranks Test. The results reveal that neither stock prices nor stock returns indicated a difference in the 5 days before and after the date of the announcement of the emergency PPKM. This shows that the announcement does not contain relevant information for investors. This may be because investors have made adjustments due to the effect of the pandemic Covid-19 in the initial phase of the corona outbreak in Indonesia.